Amongst the Resources Mobilised By The Student To Plan His Traineeship, What Role Does He Foresee for His Institutional Trainer? - Deprit, Agnès; März, Virginie; Van Nieuwenhoven, Catherine (Swiss Journal of Educational Research, 2019)
Theoretical-practical articulation at the time of the preparation of an internship is difficult for students as there is a perceived gap between academic knowledge and the reality in the field (Caron & Portelance, 2017). In order to determine whether the trainer is the resource through which students bridge this gap, exploratory research was conducted by means of a written questionnaire. The questionnaire facilitated the identification of the resources prioritized by students who are preparing for internships. The analysis shows that students gradually distance themselves from the trainer and their coursework until they use, at the end of the curriculum, resources more external to training (library and Internet).